An analysis of the adequacy of the Traditional Courts Act in light of South Africa’s obligations under articles 2, 3, 8 and 17 of the Protocol to the African Charter on Human and Peoples’ Rights on the Rights of Women in Africa - Melato, Lerato Nthabiseng (Stellenbosch : Stellenbosch University, 2025)
Thesis (LLM)--Stellenbosch University, 2025.